Fitness Levels Alterations of Primary School Greek Children in Relation to Curricular and Extracurricular Physical Activity - Christodoulos, Αντώνης; Douda, Ελένη; Bouziotas, Κωνσταντίνος; Tokakidis, Σάββας (Inquiries in Physical Education and Sport, 2004)
The purpose of this study was to examine whether parameters related to physical fitness and health are affected from curricular and extracurricular physical activity levels. A random sample of 155 Greek Primary School pupils (age 8.1±1.3 yr, height 132.8±9.3 cm, weight 30.9±8.2 kg) was subjected to anthropometric, motor (flexibility, standing broad jump, sit ups, agility-speed), and cardiovascular health-related (aerobic fitness, physical activity) fitness assessments, at the beginning of a school year and one year later. Physical activity levels were estimated with questionnaires. Subjects were subdivided into “athletes” (n=76) and “non-athletes” (n=79). “Athletes” were participating in organized extracurricular sport-activities, while “non-athletes” were involved only in school physical education (P.E.) classes. It was found that “athletes” had a better physical fitness and health profile and dedicated more time in high intensity activities (with a metabolic equivalent of >6 METs) than the “non-athletes”. Furthermore, in both measurements a considerably higher percentage of children in the “non-athletes” group were classified as obese compared to the “athletes” group (22.7% vs. 10.5%, p<.03 and 27.8% vs. 7.9%, p<.001, respectively). It was concluded that (i) higher physical activity levels have a positive effect on selected health- and skill-related fitness parameters, and (ii) P.E. classes in Greek Primary Schools are not sufficient to bring about appropriate physiological adaptations and promote health.